Features of the Transition From the Traditional to the Criterial Assessment in Schools of Kazakhstan - Kenzhetaeva Roza; Nurzhanova Sazhila; Beimisheva Aigul; Stambekova Assel; Ryabova Ekaterina; Kulbayeva Dina (International Journal of Cognitive Research in Science, Engineering and Education, 2020)
This study discusses the features of the transition from the traditional assessment system to the criteria-based assessment in schools of Kazakhstan. The use of criterion assessment in schools in Kazakhstan contributes to the crowding out of traditional methods of assessment and leads to a new vision of the methods and technologies of the system for evaluating educational achievements. In connection with the modernization of Kazakhstan’s education, significant changes are occurring in the control and assessment activities of Kazakhstan schools, its goals, content, and technologies are changing. The problem of assessment activity is one of the most urgent problems both in pedagogical theory and in pedagogical practice. This study presents the results of empirical studies and the features of the transition to a new criteria-based assessment system for Kazakhstan. According to the results of the study, the problem of the need for professional training of future primary school teachers for the criteria-based assessment system was revealed. Results also showed that there are difficulties of applying criteria-based assessment in the practice of primary school teachers. The question of what professional knowledge, skills, and abilities an elementary school teacher must possess to successfully perform the monitoring and evaluation function was investigated. Particular attention is paid to the study of the influence of criteria-based assessment on learning motivation in primary school.